SUCCESSFUL MEDICAL MANAGEMENT OF RETICULAR ABSCESS IN A CALF - M. Naveena; T. Ramasamy; C. S. Arunaman; K.S. Sriraam; B. Anurag; M.R. Srinivasan (Indian Journal of Veterinary and Animal Sciences Research, 2025)
A Seven - month old female Kankrej calf was presented to Large Animal Clinics - Out-Patient - Medicine Unit of Madras Veterinary College Teaching Hospital, Chennai, with the history of recurrent tympany for two months with scanty dung with a pasty consistency. Onclinical examination of the animal, bilateral distension of the abdomen was noticed. Haematobiochemistry revealed neutrophilia with leucocytosis and significantly elevated Gamma-Glutamyl-Transferase values. In radiography, no change in the silhouette of reticulum could be appreciated other than a mild bronchial pattern. Ultrasonography revealed an anechoic encapsulated cavity with echogenic internal spots of the reticular wall. Based on these findings, the calf was diagnosed with an abscess in the reticulum. Accordingly, the abscess was drained and the animal was treated with antibiotics and supportive therapy and the animal recovered uneventfully.